Lithium ion battery and electric equipment

By adjusting the ratio of the positive electrode material, lithium salts and film-forming agents in the lithium-ion battery, the problem of poor circulation performance of lithium manganese iron phosphate or lithium iron phosphate doped ternary material batteries is solved, and higher circulation performance, rate performance and safety performance are achieved.

CN119581672AActive Publication Date: 2025-03-07EVE POWER CO LTD

Patent Information

Application Number
CN202411629583.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-03-07
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

Lithium-ion batteries with lithium manganese iron phosphate or lithium iron phosphate doped ternary materials have poor circulation performance.

Method used

By controlling the relationship between the mass ratio of lithium phosphate positive electrode material and nickel-cobalt-manganese lithium oxide, the molar concentration of lithium hexafluorophosphate and lithium bisfluorosulfonimide in the electrolyte, and the mass ratio of positive electrode film forming agent and negative electrode film forming agent, the ratio of positive electrode film forming agent and negative electrode film forming agent in the lithium ion battery is adjusted.

Benefits of technology

It improves the cycle performance of the battery, while improving the rate performance and energy density, ensuring the safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581672A_ABST
    Figure CN119581672A_ABST
Patent Text Reader

Abstract

The invention provides a lithium ion battery and electric equipment, the lithium ion battery comprises a positive pole piece and an electrolyte, active substances in the positive pole piece comprise a phosphate lithium positive pole material and nickel cobalt manganese lithium oxide, and the electrolyte comprises a positive pole film-forming agent, a negative pole film-forming agent and a lithium salt, the lithium salt comprises lithium hexafluorophosphate and lithium bis (fluorosulfonyl) imide, the lithium ion battery meets the following formula: # imgabs0 #, NL is the mass ratio of the lithium nickel cobalt manganese oxide to the lithium phosphate positive electrode material, Salt is the sum of the molar concentrations of the lithium hexafluorophosphate and the lithium bis (fluorosulfonyl) imide in the electrolyte by taking mol / L as the unit, and the sum of the molar concentrations of the lithium hexafluorophosphate and the lithium bis (fluorosulfonyl) imide in the electrolyte is the sum of the molar concentrations of the lithium hexafluorophosphate and the lithium bis (fluorosulfonyl) imide. Add is the mass ratio of the positive electrode film-forming agent to the negative electrode film-forming agent. When the ternary material is doped in the lithium manganese iron phosphate or the lithium iron phosphate, the proportion of the positive and negative electrode film-forming agents and the proportion of the heat-resistant high-lithium salt can be adjusted according to the mixing proportion of the lithium manganese iron phosphate and the lithium iron phosphate, so that the cycle performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a lithium-ion battery and electrical equipment. Background Art

[0002] As people's requirements for environmental protection and energy conservation become higher and higher, the replacement of power battery materials has become more and more urgent. The new material combining ternary materials with lithium iron manganese phosphate or lithium iron phosphate will become an important development direction in the future. The advantages of this material are mainly reflected in the higher energy density than pure lithium iron manganese phosphate, and higher safety and lower cost than pure ternary materials. As the mixing ratio of ternary materials increases, the rate performance and energy density of the battery are getting better and better, but it has an adverse effect on the cycle performance of the battery. Summary of the invention

[0003] The embodiments of the present invention provide a lithium-ion battery and an electrical device, which can improve the technical problem of poor cycle performance of lithium manganese iron phosphate or lithium iron phosphate doped ternary materials in the related art.

[0004] In a first aspect, an embodiment of the present invention provides a lithium ion battery, comprising a positive electrode plate and an electrolyte, wherein the active material in the positive electrode plate comprises a lithium phosphate positive electrode material and nickel cobalt manganese lithium oxide, the electrolyte comprises a positive electrode film former, a negative electrode film former and a lithium salt, the lithium salt comprises lithium hexafluorophosphate and bis(fluorosulfonyl)imide lithium salt, and the lithium ion battery satisfies the following formula:

[0005] Wherein, NL is the mass ratio of the nickel cobalt manganese oxide to the lithium phosphate positive electrode material, S alt is the molar concentration of the lithium hexafluorophosphate and the bis(fluorosulfonyl)imide lithium salt in the electrolyte in mol / L, A dd is the mass ratio of the positive electrode film-forming agent to the negative electrode film-forming agent.

[0006] In one embodiment, the molar concentration ratio of the lithium hexafluorophosphate and the bis(fluorosulfonyl)imide lithium salt in the electrolyte decreases as the NL increases.

[0007] In one embodiment, the NL and the A dd Satisfaction: A dd =a·NL-0.588, wherein a is 7.1 to 13.8; and / or

[0008] The NL and the S alt Satisfaction: S alt =b·NL+1.124, where b is -0.750 to -0.456.

[0009] In one embodiment, the Add 0.1 to 3.1; and / or

[0010] The NL is 0.05 to 0.43; and / or

[0011] The S alt It is 0.85~1.1.

[0012] In one embodiment, the molar concentration ratio of the lithium hexafluorophosphate to the lithium bis(fluorosulfonyl)imide salt in the electrolyte is 0.7 to 3.4; and / or

[0013] The concentration of lithium hexafluorophosphate in the electrolyte is 0.35 mol / L to 0.85 mol / L; and / or

[0014] The concentration of the bis(fluorosulfonyl)imide lithium salt in the electrolyte is 0.25 mol / L to 0.50 mol / L.

[0015] In one embodiment, the mass percentage of the positive electrode film-forming agent in the electrolyte is 0.2% to 2.5%; and / or

[0016] The mass percentage of the negative electrode film-forming agent in the electrolyte is 0.8% to 2.0%.

[0017] In one embodiment, the lithium phosphate positive electrode material includes one or more of lithium manganese iron phosphate and lithium iron phosphate; and / or

[0018] The positive electrode film-forming agent includes one or more of 1,3-propane sultone, lithium difluorooxalatoborate, lithium bis(oxalate)borate, tris(trimethylsilyl)phosphite, methylene disulfonate, tris(trimethylsilyl)borate and hexanetricarbonitrile; and / or

[0019] The negative electrode film-forming agent includes one or more of vinylene carbonate, fluoroethylene carbonate, lithium difluorophosphate, lithium tetrafluoroborate and vinyl sulfate.

[0020] In one embodiment, the single-sided surface density of the positive electrode sheet is 200 g / m 2 ~260g / m 2 ; and / or

[0021] The compaction density of the positive electrode sheet is 2.0 g / cm 3 ~2.6g / cm 3 ; and / or

[0022] The injection coefficient of the lithium ion battery is 3.0 g / Ah to 5.0 g / Ah.

[0023] In one embodiment, the lithium-ion battery further comprises a negative electrode plate, and the active material of the negative electrode plate comprises graphite;

[0024] The single surface density of the negative electrode sheet is 80g / m 2 ~110g / m 2 ; and / or

[0025] The compaction density of the negative electrode sheet is 1.55 g / cm 3 ~1.75g / cm 3 .

[0026] In a second aspect, an embodiment of the present invention provides an electrical device including the above-mentioned lithium-ion battery.

[0027] Beneficial effects of the embodiments of the present invention:

[0028] In an embodiment of the present invention, by controlling the relationship among the mass ratio of lithium phosphate positive electrode material and nickel cobalt manganese lithium oxide in a lithium-ion battery, the molar concentration of lithium hexafluorophosphate and bis(fluorosulfonyl)imide lithium salt in the electrolyte, and the mass ratio of the positive electrode film-forming agent to the negative electrode film-forming agent, when doping ternary materials into lithium manganese iron phosphate or lithium iron phosphate, the ratio of the positive and negative electrode film-forming agents and the ratio of the high heat-resistant lithium salt can be adjusted according to the mixing ratio of the two, thereby improving the cycle performance of the battery. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention. In the present invention, unless otherwise specified, the directional words used, such as "upper" and "lower", generally refer to the upper and lower parts of the device in actual use or working state; while "inside" and "outside" refer to the outline of the device.

[0030] As the blending ratio of ternary materials in lithium manganese iron phosphate or lithium iron phosphate increases, the battery's rate performance and energy density become better and better, but it has an adverse effect on the battery's safety performance.

[0031] The technical solution of this application is as follows:

[0032] In a first aspect, an embodiment of the present application provides a lithium-ion battery, comprising a positive electrode plate and an electrolyte, wherein the active material in the positive electrode plate comprises a lithium phosphate positive electrode material and nickel cobalt manganese lithium oxide (NCM), the electrolyte comprises a positive electrode film-forming agent, a negative electrode film-forming agent and a lithium salt, the lithium salt comprises lithium hexafluorophosphate (LiPF6) and bis(fluorosulfonyl)imide lithium salt (LiFSI), and the lithium-ion battery satisfies the following formula:

[0033] Wherein, NL is the mass ratio of the nickel cobalt manganese lithium oxide to the lithium phosphate positive electrode material, S alt is the molar concentration of the lithium hexafluorophosphate and the bis(fluorosulfonyl)imide lithium salt in the electrolyte in mol / L, A dd is the mass ratio of the positive electrode film-forming agent to the negative electrode film-forming agent.

[0034] In the present application, by controlling the mass ratio of lithium phosphate positive electrode material and nickel cobalt manganese lithium oxide in lithium-ion batteries, the molar concentration of lithium hexafluorophosphate and bis(fluorosulfonyl)imide lithium salt in the electrolyte, and the mass ratio of positive electrode film former and negative electrode film former, when doping ternary materials in lithium phosphate positive electrode materials, the ratio of positive and negative electrode film formers and the ratio of high heat-resistant lithium salts can be adjusted according to the blending ratio of the two, thereby improving the battery rate performance and energy density while improving the battery cycle performance. The higher the blending ratio of nickel cobalt manganese lithium oxide in the positive electrode sheet, that is, the larger the NL, the less negative electrode film former can be, the more positive electrode film former can be increased, that is, the A is increased. dd , thereby solving the problem that the thermal stability of NCM is worse than that of lithium phosphate positive electrode materials, and at the same time reducing the concentration of lithium salt. High concentration of lithium salt is more likely to cause thermal runaway than low concentration of lithium salt.

[0035] The sum of the concentrations of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide in the electrolyte refers to the sum of the concentrations of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide in the electrolyte before the battery is filled with electrolyte. The mass ratio of the positive electrode film-forming agent to the negative electrode film-forming agent refers to the mass ratio of the positive electrode film-forming agent to the negative electrode film-forming agent in the electrolyte before the battery is filled with electrolyte. It can be 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.59, etc.

[0036] In some embodiments, the lithium-ion battery satisfies: It can be 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.57, etc.

[0037] In some embodiments, the lithium phosphate positive electrode material includes one or more of lithium manganese iron phosphate and lithium iron phosphate.

[0038] In some embodiments, the NL is 0.05 to 0.43, for example, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.43, etc. In this way, the energy density and rate performance of the battery can be improved while ensuring the safety and long cycle performance of the battery. Adding nickel cobalt manganese lithium oxide (NCM) to lithium iron manganese phosphate or lithium iron phosphate, if too much NCM is added, will affect the safety performance of the battery, if less NCM is added, the energy density and rate performance of the battery will increase less.

[0039] In some embodiments, the NL is 0.1 to 0.3, for example, it can be 0.1, 0.12, 0.15, 0.17, 0.2, 0.22, 0.25, 0.27, 0.3, etc.

[0040] In some embodiments, the NL and the A dd Satisfaction: A dd =a·NL-0.588, wherein a is 7.1 to 13.8, for example, 7.1, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 13.8, etc. Thus, when NL is larger, that is, the content of nickel cobalt manganese lithium (NCM) in the positive electrode sheet is more, and the content of lithium iron manganese phosphate or lithium iron phosphate is less, the corresponding A dd The larger the value, the more positive electrode film-forming agent is added to the electrolyte, and the less negative electrode film-forming agent is added, so that the amount of positive electrode film-forming agent added can be increased with the increase of nickel cobalt manganese lithium (NCM) content, and the amount of negative electrode film-forming agent added can be reduced with the decrease of lithium iron manganese phosphate or lithium iron phosphate content, thereby strengthening the protection of the positive electrode and controlling the thickness of the negative electrode film to control the battery impedance. If the content of lithium iron manganese phosphate or lithium iron phosphate is reduced, but the amount of negative electrode film-forming agent is not reduced, the negative electrode film-forming agent will be redundant, resulting in a thicker negative electrode film and increased impedance.

[0041] In some embodiments, a is 7.35 to 8.66, for example, 7.4, 7.5, 7.6, 7.7, 7.8, 7.9, 8.0, 8.1, 8.2, 8.3, 8.4, 8.5, 8.6, etc.

[0042] In some embodiments, the A dd is 0.1 to 3.1, for example, 0.1, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.1, etc. In this way, both the positive electrode and the negative electrode can be protected. ddIf it is too small, the protection effect on the positive electrode will be insufficient. dd If it is too large, the protection of the negative electrode will be insufficient, and the unstable film formation of the positive and negative electrodes will deteriorate the cycle performance of the battery.

[0043] In some embodiments, the A dd It is 0.3 to 2.0, for example, it may be 0.3, 0.5, 0.7, 1.0, 1.2, 1.5, 1.7, 2.0, etc.

[0044] In some embodiments, the mass percentage of the positive electrode film-forming agent in the electrolyte is 0.2% to 2.5%, for example, 0.2%, 0.5%, 0.7%, 1%, 1.2%, 1.5%, 1.7%, 2%, 2.2%, 2.5%, etc. In this way, the positive electrode can be fully protected.

[0045] In some embodiments, the mass percentage of the positive electrode film-forming agent in the electrolyte is 0.5% to 2.0%, for example, 0.5%, 0.7%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2.0%, etc. In this way, the positive electrode can be fully protected.

[0046] In some embodiments, the mass percentage of the negative electrode film-forming agent in the electrolyte is 0.8% to 2.0%, for example, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, etc. In this way, the negative electrode can be fully protected.

[0047] In some embodiments, the mass percentage of the negative electrode film-forming agent in the electrolyte is 1.0% to 1.8%, for example, it can be 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, etc.

[0048] In some embodiments, the positive electrode film-forming agent includes one or more of 1,3-propane sultone (PS), lithium difluorooxalatoborate (LiDFOB), lithium bis(oxalate)borate (LiBOB), tri(trimethylsilyl)phosphite (TMSP), methylene disulfonate (MMDS), tri(trimethylsilyl)borate (TMSB) and hexanetricarbonitrile (HTCN). In this way, a cathode electrolyte interphase (CEI) film can be effectively formed on the surface of the positive electrode sheet, covering the active sites, reducing the contact between the electrolyte and the electrode, reducing the decomposition of the electrolyte and the positive electrode material in the high potential area, maintaining the stability of the positive electrode material, and improving the battery capacity and cycle performance.

[0049] In some embodiments, the negative electrode film-forming agent includes one or more of vinylene carbonate (VC), fluoroethylene carbonate (FEC), lithium difluorophosphate (LiPO2F2), lithium tetrafluoroborate (LiBF4) and vinyl sulfate (DTD). In this way, a stable solid electrolyte interface (SEI) film can be formed on the surface of the negative electrode plate, so that it has good electronic insulation, only allows lithium ions to pass through, and prevents the electrolyte from further reacting with the electrode material, thereby protecting the electrode material, extending the cycle life of the battery, and improving the safety of the battery.

[0050] In some embodiments, the NL and the S alt Satisfaction: S alt = b·NL+1.124, wherein b is -0.750 to -0.456, for example, -0.456, -0.500, -0.550, -0.600, -0.650, -0.700, -0.750, etc. Thus, when NL is larger, that is, the content of nickel cobalt manganese lithium (NCM) in the positive electrode sheet is higher, and the content of lithium iron manganese phosphate or lithium iron phosphate is lower, the corresponding S alt The smaller the total concentration of lithium salt, the better the thermal stability of the battery, thus improving the safety of the battery. Thermal runaway of high-concentration lithium salt will reduce the battery temperature, so the concentration of lithium salt needs to be controlled.

[0051] In some embodiments, b is -0.639 to -0.690, for example, it may be -0.639, -0.640, -0.640, -0.650, -0.660, -0.670, -0.680, -0.690, etc.

[0052] In some embodiments, the S alt It is 0.85 to 1.10, for example, it can be 0.85, 0.87, 0.90, 0.92, 0.95, 0.97, 1.00, 1.02, 1.05, 1.07, 1.10, etc. In this way, the lithium salt concentration in the electrolyte can be controlled, thereby reducing the probability of thermal runaway caused by high concentration of lithium salt and improving the safety performance of the battery.

[0053] In some embodiments, the S alt It is 0.90 to 1.05, for example, it may be 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1.00, 1.01, 1.02, 1.03, 1.04, 1.05, etc.

[0054] In some embodiments, the molar concentration ratio of the lithium hexafluorophosphate and the bis(fluorosulfonyl)imide lithium salt in the electrolyte decreases as the NL increases. In this way, when the NL is larger, that is, the content of nickel cobalt manganese (NCM) in the positive electrode plate is higher, the content of lithium iron manganese phosphate or lithium iron phosphate is lower, increasing the proportion of LiFSI in the lithium salt and reducing the proportion of LiPF6 can improve the thermal stability of the battery, thereby improving the safety performance of the battery. As the amount of NCM added to the battery increases, the thermal stability of the battery will decrease. The thermal stability of LiFSI is better than that of LiPF6. Increasing the proportion of LiFSI can improve the thermal stability of the battery.

[0055] In some embodiments, the molar concentration ratio of the lithium hexafluorophosphate and the bis(fluorosulfonyl)imide lithium salt in the electrolyte is 0.7 to 3.4, for example, 0.7, 1.0, 1.2, 1.5, 1.7, 2.0, 2.2, 2.5, 2.7, 3.0, 3.4, etc.

[0056] In some embodiments, the concentration ratio of the lithium hexafluorophosphate and the bis(fluorosulfonyl)imide lithium salt in the electrolyte is 1.0 to 2.5, for example, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, etc.

[0057] In some embodiments, the concentration of lithium hexafluorophosphate in the electrolyte is 0.35 mol / L to 0.85 mol / L, for example, 0.35 mol / L, 0.45 mol / L, 0.55 mol / L, 0.65 mol / L, 0.75 mol / L, 0.85 mol / L, etc. In this way, LiPF6 can passivate the aluminum foil, reduce the corrosion of the aluminum foil by LiFSI, and reduce the probability of LiPF6 hydrolyzing to generate HF, thereby improving the stability of the battery.

[0058] In some embodiments, the concentration of lithium hexafluorophosphate in the electrolyte is 0.45 mol / L to 0.75 mol / L, for example, 0.45 mol / L, 0.50 mol / L, 0.55 mol / L, 0.60 mol / L, 0.65 mol / L, 0.70 mol / L, 0.75 mol / L, etc.

[0059] In some embodiments, the concentration of the bis(fluorosulfonyl)imide lithium salt in the electrolyte is 0.25 mol / L to 0.50 mol / L, for example, 0.25 mol / L, 0.3 mol / L, 0.35 mol / L, 0.4 mol / L, 0.45 mol / L, 0.5 mol / L, etc. In this way, the corrosion of LiFSI on the aluminum foil can be controlled, the cycle performance of the battery can be improved, and the stability and conductivity of the electrolyte can be improved.

[0060] In some embodiments, the concentration of the bisfluorosulfonyl imide lithium salt in the electrolyte is 0.30 mol / L to 0.45 mol / L, for example, 0.30 mol / L, 0.31 mol / L, 0.32 mol / L, 0.33 mol / L, 0.34 mol / L, 0.35 mol / L, 0.36 mol / L, 0.37 mol / L, 0.38 mol / L, 0.39 mol / L, 0.40 mol / L, 0.41 mol / L, 0.42 mol / L, 0.43 mol / L, 0.44 mol / L, 0.45 mol / L, etc.

[0061] In some embodiments, the single-sided surface density of the positive electrode sheet is 200 g / m 2 ~260g / m 2 , for example, it can be 200g / m 2 , 210g / m 2 , 220g / m 2 , 230g / m 2 , 240g / m 2 , 250g / m 2 , 260g / m 2 In this way, the battery can have a higher energy density, and too high surface density will affect the transmission of lithium ions, increase battery impedance, and deteriorate battery cycle performance.

[0062] In some embodiments, the single-sided surface density of the positive electrode sheet is 210 g / m 2 ~250g / m 2 , for example, it can be 210g / m 2 , 220g / m 2 , 230g / m 2 , 240g / m 2 , 250g / m 2 wait.

[0063] In some embodiments, the compaction density of the positive electrode sheet is 2.0 g / cm 3 ~2.6g / cm 3 , for example, it can be 2.0 g / cm 3 , 2.1g / cm3 , 2.2g / cm 3 , 2.3g / cm 3 , 2.4g / cm 3 , 2.5g / cm 3 , 2.6g / cm 3 In this way, the battery can have a higher energy density, and too high compaction will crush the particles and destroy the effectiveness of the active material.

[0064] In some embodiments, the compaction density of the positive electrode sheet is 2.1 g / cm 3 ~2.5g / cm 3 , for example, it can be 2.1 g / cm 3 , 2.2g / cm 3 , 2.3g / cm 3 , 2.4g / cm 3 , 2.5g / cm 3 wait.

[0065] In some embodiments, the injection coefficient of the lithium-ion battery is 3.0 g / Ah to 5.0 g / Ah, for example, 3.0 g / Ah, 3.2 g / Ah, 3.5 g / Ah, 3.8 g / Ah, 4.0 g / Ah, 4.2 g / Ah, 4.5 g / Ah, 4.8 g / Ah, 5.0 g / Ah, etc. In this way, the battery performance can be improved. Too much electrolyte will lead to more side reactions and increase the battery cost. Too little electrolyte will lead to insufficient electrode wetting, increased interface impedance, and deterioration of battery cycle performance.

[0066] In some embodiments, the filling coefficient of the lithium-ion battery is 3.5g / Ah to 4.5g / Ah, for example, it can be 3.5g / Ah, 3.6g / Ah, 3.7g / Ah, 3.8g / Ah, 3.9g / Ah, 4.0g / Ah, 4.1g / Ah, 4.2g / Ah, 4.3g / Ah, 4.4g / Ah, 4.5g / Ah, etc.

[0067] In some embodiments, the lithium-ion battery further comprises a negative electrode plate, and the active material of the negative electrode plate comprises graphite. In this way, the battery performance can be improved. Graphite has a low cost and has high specific energy, good chemical stability and a long cycle life.

[0068] In some embodiments, the single-sided surface density of the negative electrode sheet is 80 g / m 2 ~110g / m 2 , for example, it can be 80g / m 2 , 90g / m 2 , 100g / m 2 , 110g / m 2In this way, the battery can have a higher energy density, and too high surface density will affect the transmission of lithium ions, increase battery impedance, and deteriorate battery cycle performance.

[0069] In some embodiments, the compaction density of the negative electrode sheet is 1.55 g / cm 3 ~1.75g / cm 3 , for example, it can be 1.55 g / cm 3 , 1.57g / cm 3 , 1.6g / cm 3 , 1.62g / cm 3 , 1.65g / cm 3 , 1.67g / cm 3 , 1.7g / cm 3 , 1.72g / cm 3 , 1.75g / cm 3 In this way, the battery can have a higher energy density, and too high compaction will crush the particles and destroy the effectiveness of the active material.

[0070] An embodiment of the present application also provides an electrical device, comprising the above-mentioned lithium-ion battery.

[0071] Example 1

[0072] A lithium-ion battery (a soft-pack battery with a model number of 505070), wherein the active material in the positive electrode plate is lithium iron manganese phosphate and lithium nickel cobalt manganese (NCM), and the mass ratio (NL) of lithium iron manganese phosphate and lithium nickel cobalt manganese is 0.25%, the positive electrode film-forming agent is methylene methanedisulfonate (MMDS), and the mass percentage of MMDS in the electrolyte before injection is 1.5%, the negative electrode film-forming agent is vinylene carbonate (VC), and the mass percentage of VC in the electrolyte before injection is 1.2%, the concentration of lithium hexafluorophosphate (LiPF6) in the electrolyte is 0.55 mol / L, and the concentration of lithium bis(fluorosulfonyl)imide (LiFSI) in the electrolyte is 0.4 mol / L.

[0073] Example 2

[0074] This embodiment is basically the same as Example 1, with the only difference that the mass ratio (NL) of lithium manganese iron phosphate and lithium nickel cobalt manganese oxide in this embodiment is 0.17%, the mass percentage of the positive electrode film-forming agent is 1.0%, the mass percentage of the negative electrode film-forming agent is 1.5%, the concentration of lithium hexafluorophosphate (LiPF6) is 0.65 mol / L, and the concentration of lithium bis(fluorosulfonyl)imide (LiFSI) is 0.35 mol / L.

[0075] Example 3

[0076] This embodiment is basically the same as Example 1, with the only difference that the mass ratio (NL) of lithium manganese iron phosphate and lithium nickel cobalt manganese oxide in this embodiment is 0.14%, the mass percentage of the positive electrode film-forming agent is 0.75%, the mass percentage of the negative electrode film-forming agent is 1.65%, the concentration of lithium hexafluorophosphate (LiPF6) is 0.7 mol / L, and the concentration of lithium bis(fluorosulfonyl)imide (LiFSI) is 0.32 mol / L.

[0077] Example 4

[0078] This embodiment is basically the same as Example 1, with the only difference that the mass ratio (NL) of lithium manganese iron phosphate and lithium nickel cobalt manganese oxide in this embodiment is 0.05%, the mass percentage of the positive electrode film-forming agent is 0.2%, the mass percentage of the negative electrode film-forming agent is 2%, the concentration of lithium hexafluorophosphate (LiPF6) is 0.85 mol / L, and the concentration of lithium bis(fluorosulfonyl)imide (LiFSI) is 0.25 mol / L.

[0079] Example 5

[0080] This embodiment is basically the same as Example 1, with the only difference that the mass ratio (NL) of lithium manganese iron phosphate and lithium nickel cobalt manganese oxide in this embodiment is 0.43%, the mass percentage of the positive electrode film-forming agent is 2.5%, the mass percentage of the negative electrode film-forming agent is 0.8%, the concentration of lithium hexafluorophosphate (LiPF6) is 0.35 mol / L, and the concentration of lithium bis(fluorosulfonyl)imide (LiFSI) is 0.5 mol / L.

[0081] Example 6

[0082] This embodiment is basically the same as Example 1, with the only difference that the mass ratio (NL) of lithium manganese iron phosphate and lithium nickel cobalt manganese oxide in this embodiment is 0.1%, the mass percentage of the positive electrode film-forming agent is 0.5%, the mass percentage of the negative electrode film-forming agent is 1.8%, the concentration of lithium hexafluorophosphate (LiPF6) is 0.75 mol / L, and the concentration of lithium bis(fluorosulfonyl)imide (LiFSI) is 0.3 mol / L.

[0083] Example 7

[0084] This embodiment is basically the same as Example 1, with the only difference that the mass ratio (NL) of lithium manganese iron phosphate and lithium nickel cobalt manganese oxide in this embodiment is 0.3%, the mass percentage of the positive electrode film-forming agent is 2%, the mass percentage of the negative electrode film-forming agent is 1%, the concentration of lithium hexafluorophosphate (LiPF6) is 0.45 mol / L, and the concentration of lithium bis(fluorosulfonyl)imide (LiFSI) is 0.45 mol / L.

[0085] Example 8

[0086] This embodiment is basically the same as Example 1, with the only difference that the mass ratio (NL) of lithium manganese iron phosphate and lithium nickel cobalt manganese oxide in this embodiment is 0.13%, the mass percentage of the positive electrode film-forming agent is 0.7%, the mass percentage of the negative electrode film-forming agent is 1.8%, the concentration of lithium hexafluorophosphate (LiPF6) is 0.73 mol / L, and the concentration of lithium bis(fluorosulfonyl)imide (LiFSI) is 0.3 mol / L.

[0087] Example 9

[0088] This embodiment is basically the same as Embodiment 1, except that the concentration of lithium hexafluorophosphate (LiPF6) in this embodiment is 0.7 mol / L, and the concentration of lithium bis(fluorosulfonyl)imide (LiFSI) is 0.5 mol / L.

[0089] Example 10

[0090] This embodiment is basically the same as Embodiment 1, except that the concentration of lithium hexafluorophosphate (LiPF6) in this embodiment is 0.9 mol / L, and the concentration of lithium bis(fluorosulfonyl)imide (LiFSI) is 0.05 mol / L.

[0091] Comparative Example 1

[0092] This comparative example is substantially the same as Example 1, except that the mass percentage content of the positive electrode film-forming agent in this comparative example is 0.3%.

[0093] Comparative Example 2

[0094] This comparative example is substantially the same as Example 1, except that the mass percentage content of the negative electrode film-forming agent in this comparative example is 0.4%.

[0095] Test example:

[0096] 25℃ cycle test: The batteries of the embodiment and the comparative example were fully charged and discharged at 25℃. The test steps are: 30min of standby; constant current and constant voltage charging, the current is 0.33C, the constant voltage is 4.25V, and the cut-off current is 0.05C (C is the battery design capacity), and the capacity of the last cycle is recorded as the calibrated capacity Q after three cycles. Standby for 1h, constant current and constant voltage charging, the current is 1Q, the constant voltage is 4.25V, and the cut-off current is 0.05Q; standby for 1h; constant current discharge, the current is 1Q, cycle 1000 times, and measure the capacity retention rate, as shown in Table 1.

[0097] Soft pack puncture test: A high temperature resistant steel needle with a diameter of 7 mm is used for the fully charged single cell of the battery of the embodiment and the comparative example. The needle tip cone angle is 48°. The needle is pierced at a speed of 25 mm / s from the direction perpendicular to the battery plate. The penetration position is close to the geometric center of the pierced surface. The steel needle stays in the lithium battery and is observed for one hour. The judgment basis is that the battery does not catch fire or explode. All the above batteries do not catch fire. Therefore, the risk of puncture is judged by the maximum temperature of the large surface after one hour. The test method for the maximum temperature of the large surface is to directly attach the puncture temperature sensor to the large surface shell and record the temperature, as shown in Table 1.

[0098] Table 1

[0099]

[0100] From Table 1 we can see that:

[0101] Compared with Example 9 and Example 10, the battery of Example 1 to Example 8 has a higher capacity retention rate and a lower shell surface temperature. The reason is that, in the battery of Example 1 to Example 8, as the proportion of nickel cobalt manganese oxide (NCM) mixed in lithium iron manganese phosphate increases, the mass percentage of the positive electrode film-forming agent increases accordingly, and the mass percentage of the negative electrode film-forming agent decreases, that is, A dd As a result, the total concentration of lithium hexafluorophosphate (LiPF6) and bis(fluorosulfonyl)imide lithium salt decreased accordingly, that is, S alt The total concentration of lithium hexafluorophosphate (LiPF6) and bis(fluorosulfonyl)imide lithium salt in Example 9 is relatively high, which results in a small improvement in the cycle performance and safety performance of the battery. The ratio of LiPF6 / LiFSI in Example 10 is relatively high, which results in a small improvement in the cycle performance and safety performance of the battery.

[0102] Compared with Comparative Example 1, the capacity retention rate of the battery in Example 1 is higher, because the mass percentage of the positive electrode film-forming agent in Comparative Example 1 is smaller, so The larger the value, the poorer the film-forming protection effect of the positive electrode film-forming agent, which in turn deteriorates the battery cycle performance.

[0103] Compared with Comparative Example 2, the capacity retention rate of the battery in Example 1 is higher. The reason is that the mass percentage of the negative electrode film-forming agent in Comparative Example 1 is smaller, so The smaller the value, the poorer the film-forming protection effect of the negative electrode film-forming agent, which in turn deteriorates the battery cycle performance.

[0104] The embodiments of the present invention are described in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.

Claims

1. A lithium ion battery, characterized in that: The invention comprises a positive electrode sheet and an electrolyte, wherein the active material in the positive electrode sheet comprises a lithium phosphate positive electrode material and nickel cobalt manganese lithium oxide, the electrolyte comprises a positive electrode film former, a negative electrode film former and a lithium salt, the lithium salt comprises lithium hexafluorophosphate and bis(fluorosulfonyl)imide lithium salt, and the lithium ion battery satisfies the following formula: Wherein, NL is the mass ratio of the nickel cobalt manganese lithium oxide to the lithium phosphate positive electrode material, S alt is the molar concentration of the lithium hexafluorophosphate and the bis(fluorosulfonyl)imide lithium salt in the electrolyte in mol / L, A dd is the mass ratio of the positive electrode film-forming agent to the negative electrode film-forming agent.

2. The lithium-ion battery according to claim 1, wherein: The molar concentration ratio of the lithium hexafluorophosphate and the bis(fluorosulfonyl)imide lithium salt in the electrolyte decreases as the NL increases.

3. The lithium ion battery according to claim 1, characterized in that The NL and the A dd Satisfaction: A dd =a·NL-0.588, wherein a is 7.1 to 13.8; and / or The NL and the S alt Satisfaction: S alt =b·NL+1.124, where b is -0.750 to -0.

456.

4. The lithium ion battery according to claim 1, characterized in that The A dd 0.1 to 3.1; and / or The NL is 0.05 to 0.43; and / or The S alt It is 0.85~1.

1.

5. The lithium ion battery according to claim 1, characterized in that The molar concentration ratio of the lithium hexafluorophosphate to the bis(fluorosulfonyl)imide lithium salt in the electrolyte is 0.7 to 3.4; and / or The concentration of lithium hexafluorophosphate in the electrolyte is 0.35 mol / L to 0.85 mol / L; and / or The concentration of the bis(fluorosulfonyl)imide lithium salt in the electrolyte is 0.25 mol / L to 0.50 mol / L.

6. The lithium-ion battery according to claim 1, wherein: The mass percentage of the positive electrode film-forming agent in the electrolyte is 0.2% to 2.5%; and / or The mass percentage of the negative electrode film-forming agent in the electrolyte is 0.8% to 2.0%.

7. The lithium-ion battery according to claim 1, wherein: The lithium phosphate positive electrode material includes one or more of lithium manganese iron phosphate and lithium iron phosphate; and / or The positive electrode film-forming agent includes one or more of 1,3-propane sultone, lithium difluorooxalatoborate, lithium bis(oxalate)borate, tris(trimethylsilyl)phosphite, methylene disulfonate, tris(trimethylsilyl)borate and hexanetricarbonitrile; and / or The negative electrode film-forming agent includes one or more of vinylene carbonate, fluoroethylene carbonate, lithium difluorophosphate, lithium tetrafluoroborate and vinyl sulfate.

8. The lithium-ion battery according to claim 1, wherein: The single-sided surface density of the positive electrode sheet is 200 g / m 2 ~260g / m 2 ; and / or The compaction density of the positive electrode sheet is 2.0 g / cm 3 ~2.6g / cm 3 ; and / or The liquid injection coefficient of the lithium ion battery is 3.0 g / Ah to 5.0 g / Ah.

9. The lithium ion battery according to claim 1, characterized in that The lithium-ion battery also includes a negative electrode plate: the active material of the negative electrode plate includes graphite; the single-sided surface density of the negative electrode plate is 80g / m 2 ~110g / m 2 ; and / or The compaction density of the negative electrode plate is 1.55 g / cm 3 ~1.75g / cm 3 .

10. An electrical equipment, characterized in that: It comprises a lithium ion battery as claimed in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Lithium ion battery positive electrode and lithium ion battery prepared from same

    CN115995528A

  • Positive pole piece, secondary battery, battery module, battery pack, electric device and method for balancing internal voltage difference of battery

    CN116941057A

  • Lithium manganese iron phosphate positive electrode material and preparation method thereof, positive electrode plate and preparation method thereof, lithium ion battery and electric equipment

    CN117577832A

  • Adaptive electrolyte of lithium iron manganese phosphate battery and lithium battery

    CN117832630A

  • Electrolyte for rechargeable lithium battery and rechargeable lithium battery including the same

    US20240322236A1

Cited By

  • Battery monomer, battery device, power utilization device and energy storage device

    CN122315017A

  • Battery cell, battery device, power consuming device, and energy storage device

    CN122315017B

  • Battery monomer, battery device, power utilization device and energy storage device

    CN122337993A

  • Battery cell, battery device, power consuming device, and energy storage device

    CN122337993B

  • Battery, battery assembly, and electric device

    WO2026194759A1